Environmental management system and human resource practices: is there a link between them in four Brazilian companies? - Chiappetta Jabbour, Charbel Jose [UNESP]; Almada Santos, Fernando Cesar; Nagano, Marcelo Seido (Elsevier B.V., 2008)
The aim of this article is to analyze the theoretical model proposed by [Jabbour CJC, Santos FCA. Relationships between human resource dimensions and environmental management in companies: proposal of a model. Journal of Cleaner Production 2008;16(1):5 1-8.] based on the data collected in four Brazilian companies. This model investigates how the phases of the environmental management system can be linked to human resource practices in order to attain continuous improvement of a company's environmental performance. Our aim is to contribute to a field, which has little empirical evidence. Although the interaction between the phases of the environmental management system and human resource practices is recommended by the specialized literature [Daily BE Huang S. Achieving sustainability through attention to human resource factors in environmental management. International Journal of Operations and Production Management 2001:21(12):1539-52.], the results indicate that most of the theoretical assumptions could not be confirmed in these Brazilian companies. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Environmental management system; Human resource practices; Brazilian companies